Updates from the CGIAR Initiative on Asian Mega-Deltas, Issue 1, November 2022 - CGIAR Initiative on Asian Mega-Deltas (International Rice Research Institute, 2022)
In the first issue of the CGIAR Initiative on Asian Mega-Deltas (AMD) newsletter, the publication introduced the AMD Initiative, its focus areas, and its target outcomes.